Workers' Experiences Reporting Workplace Accidents: An Analysis from the General System of Occupational Risks in Colombia - Judith Vanessa Galeano Buenaventura; Ivonne Constanza Valero-Pacheco; Natalia Eugenia Gómez Rúa; Diana Elizabeth Cuervo Díaz (Revista Colombiana de Salud Ocupacional)
Aim: To understand the experiences of workers who have reported at least one workplace accident within the General System of Occupational Risks in Colombia, focusing on injuries, sequelae, consequences, and the healthcare and economic benefits received.